Establishing a perioperative medicine for older people undergoing surgery service for general surgical patients at a district general hospital. Issue 6 (2021) - Casas, Ruth de Las; Meilak, Catherine; Whittle, Anna; Partridge, Judith; Adamek, Jacek; Sadler, Euan; Sevdalis, Nick; Dhesi, Jugdeep
No abstract available